A Novel Approach for Enhancing Security of MANET Using Trust Based Method (International Journal of Engineering and Computer Science, 2018)
Mobile Ad-hoc Networks are a collection of two or more devices equipped with wireless communication and networking capabilities without a centralized infrastructure. The open medium and wide distribution of nodes make MANET vulnerable to attack from malicious nodes. In order to reduce the hazards from these malicious nodes, concept of trust is introduced in to the MANET. Trust Mechanisms secure data forwarding by isolating nodes with malicious intentions using trust value on the nodes. Different trust mechanisms are designed to enhance the security of MANETs. In this paper, the trust model has two components: trust from direct observation and trust from indirect observation. In direct observation, observer node directly evaluates the trust value of observed node based on its own opinion. In indirect observation, instead of taking arithmetic mean of trust values from all the neighbors, this method uses Dempster-shafer theory which provides a numerical measurement of degrees of belief about a proposition from multiple sources. As observer node needs to collects opinions from all its neighbors to evaluate the trust of observed node which is not in the range of observer node, it will cause congestion in the network. Thereby indirect observation takes some delay in trust value calculation. So selective deviation test and energy consumption filtering is applied to reduce delay in the network. By reducing the delay, packet delivery ratio in the network can be increased.